LIVER FUNCTION CHANGES IN PATIENTS WITH SPONDYLOARTHRITIS TAKING NONSTEROIDAL ANTI-INFLAMMATORY DRUGS OVER A LONG PERIOD: RESULTS OF A 10-YEAR PROGRESS PROSPECTIVE STUDY - A. P. Rebrov; I. Z. Gaydukova; A. V. Aparkina; E. V. Khondkarian; A. I. Akulova (Современная ревматология)
Objective: to assess liver function changes in patients with spondyloarthritis (SpA) taking NSAIDs regularly over a long period.Patients and methods. The data obtained during a 10-year PROGRESS prospective single-center cohort study of functional status, activity, and comorbidity (including gastrointestinal tract diseases) in patients with SpA were analyzed. The data of 363 SpA patients receiving NSAIDs regularly over a long period and followed up for 10 years were also explored. The changes that had occurred over a decade in the liver enzyme levels, the number of discontinued NSAID treatments because of a persistent increase in liver enzyme levels, and the number of prescriptions of hepatoprotective agents were analyzed.Results. For 10 years, 18 patients with SpA discontinued their NSAID intake due to elevated liver enzyme levels (≥3 times greater than the reference value); during that time, the same increase in enzyme levels was observed in 2 healthy individuals (χ2 =1.39; p=0.2). In the patients with SpA as compared to the healthy individuals, the relative risk of abnormal liver function was 1.19 (95% CI, 1.009–1.405); odds ratio was 2.9 (95% CI, 0.65–12.95). There was no increased risk for discontinuation of some NSAIDs, including nimesulide (χ2 =0.03, p=0.85), the frequency of using hepatoprotective drugs was proved to be highest for diclofenac sodium, ibuprofen, nimesulide, and ketoprofen.Conclusion. The regular long-term (as long as 10 years) use of NSAIDs to treat SpA is associated with treatment discontinuation because of elevated enzyme levels in every 10 patients. The maximum rate of discontinuation of NSAIDs due to a persistent increase in liver enzyme levels is observed 6–8 years after their regular use, so long-term NSAID therapy requires continuous monitoring of hepatic safety. The longterm intake of nimesulide, as compared with other NSAIDs, is shown to be unassociated with the higher rate of its discontinuation because of worse liver function. Hepatoprotectors are less frequently prescribed to patients taking nimesulide than to those receiving diclofenac sodium or ibuprofen and more frequently to patients using meloxicam. In most cases, prescribing hepatoprotective agents to patients receiving NSAIDs does not require discontinuation of anti-inflammatory therapy.